Low-Resistivity Cobalt and Ruthenium Ultra-Thin Film Deposition Using Bipolar HiPIMS Technique. (1st March 2022) - Seo, Min; Cho, Min Kyung; Kang, Un Hyeon; Jeon, Sin Young; Lim, Sang-Ho; Han, Seung Hee
Abstract : Owing to the rapid growth of very large-scale integration technology at nanometer scales, cobalt and ruthenium interconnects are being used to solve the high-resistivity copper problem. However, with such interconnects, carbon contamination can occur during chemical vapor deposition and atomic layer deposition. Bipolar (BP) high-power impulse magnetron sputtering (HiPIMS) with a high ionization rate is an excellent vacuum process for depositing low-resistivity thin films. In this study, low-resistivity cobalt, ruthenium, and copper thin films were deposited using BP-HiPIMS, HiPIMS, and direct-current magnetron sputtering (DCMS). The resistivities of the cobalt, ruthenium, and copper thin films (<10 nm) deposited via BP-HiPIMS were 91.5, 75, and 35%, respectively, lower than the resistivities of the same film materials deposited using direct-current MS. To solve the low pass-through flux of cobalt, the target temperature was raised to the Curie temperature (approximately 1100 °C) using a thermal insulation backplate (Ti-6Al-4V), resulting in a resistivity reduction of about 73%. The study provides a novel method for the vacuum deposition of cobalt and ruthenium thin films.